THE TYPES OF ELECTRONIC MEDIA - Sotvoldiyeva Maftuna; Qamchiyeva Nazokat; Anvarbekova Gulchiroy (TADQIQOTLAR.UZ, 2023)
Abstract: This is complete about of electronic media, what is electronic media, types of electronic media, difference between of print media and electornic media.